IMPLEMENTASI COMPUTER CLUSTER BERBASIS OPEN SOURCE UNTUK PENYEIMBANG BEBAN SISTEM DAN JARINGAN KOMPUTER - Yudhi Arta (Jurnal Teknik Informatika dan Sistem Informasi, 2016)
The importance of an information currently required a system capable of providing the best service, especially information service with the websites media. Increasing the amount of access to the website resulting into increased workload webserver and can not be solved with a single server. This problem can be resolved by applying the cluster load balance method. Basically cluster load balance work by sharing webserver workload is distrubuted to multiple server nodes so that the websites becomes balanced.Weight round robin scheduling algorithm can balance the load by determining the amount of weight to each server node. With the load balance by using a scheduling algorithm is expected to prevent the overload requests, workload leveling webserver, and speed up the response time and throughput of the performance webservers.